2017
DOI: 10.1186/s12910-016-0161-x
|View full text |Cite
|
Sign up to set email alerts
|

The intention to disclose medical errors among doctors in a referral hospital in North Malaysia

Abstract: BackgroundIn this study, medical errors are defined as unintentional patient harm caused by a doctor’s mistake. This topic, due to limited research, is poorly understood in Malaysia. The objective of this study was to determine the proportion of doctors intending to disclose medical errors, and their attitudes/perception pertaining to medical errors.MethodsThis cross-sectional study was conducted at a tertiary public hospital from July- December 2015 among 276 randomly selected doctors. Data was collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Any option selected as not reporting in the scenarios would deem the nurses to "Not report errors". These criteria were adapted from a previous study [12]. Simple logistic regression was employed to determine the factors predicting incident reporting behaviors against the outcomes of medication error disclosures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any option selected as not reporting in the scenarios would deem the nurses to "Not report errors". These criteria were adapted from a previous study [12]. Simple logistic regression was employed to determine the factors predicting incident reporting behaviors against the outcomes of medication error disclosures.…”
Section: Discussionmentioning
confidence: 99%
“…A local study [12] showed that only 10.1% of doctors in a regional referral hospital disclosed medical errors, and thus the same proportion was assumed for the reporting for nurses. Using a sample size calculator for a single proportion formula (EpiCalc 2000, v1.01) and setting the confidence interval at 95%, and the precision at 5%, the sample size required was 139.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…These errors are an occurrence within the healthcare system as a consequence of its fragmented and decentralized nature [2,3]. Medical errors can be trivial or serious and life threatening and may result in patients making fully recovery, partial recovery, or death [4]. The prevalence of medical errors around the world is high, parallel investigations that have been conducted in the nations of the United Kingdom, Australia, Italy, Switzerland, and Denmark have shown that human errors in healthcare is a serious global public health concern [5].…”
Section: Introductionmentioning
confidence: 99%